Mediação pedagógica no processo de educação pré-natal: atuação do pedagogo na perspectiva da educação popular - Vivan, Aline Moreschi (My University, 2022)
This dissertation investigates how pedagogical mediation in prenatal education can contribute from the perspective of a popular education. It is thought how to think about possibilities of supporting and potentializing the object of study that investigates the principles, the practices of care with the users in front of the public health programs. Pedagogical mediation is analyzed as a potential with prenatal education; there is the importance of mediation that stands out as a horizon for prenatal education and for popular education as a pedagogical space. I bring the following research problem: how can pedagogical mediation in prenatal education contribute from the perspective of popular education? For development, the general objective is to analyze pedagogical mediation as a potential with prenatal education, based on the perspective of popular education. In order to reach the general objective, specific objectives were selected: to characterize radical pedagogy as a possible horizon for prenatal education; contextualize prenatal education as an experience in public health and the possible insertion of the pedagogue based on the conception of education and prenatal education; verify the importance of learning mediation for prenatal education processes; to highlight the mediation of learning as a horizon for prenatal education and popular education, in the context of health as a pedagogical space. As theoretical contribution, I present the radical themes defended by Professor PhD. Agustín de la Herrán Gascón, who analyzes the development of prenatal education from an epistemological and scientific point of view. Reuven Feuerstein, with his productions and discussions on mediation, in addition to the process as a capacity for human transformation in emotional and cognitive processes. Paulo Freire, regarding the space of excellence for popular education, offering conditions for reflection in the face of this conception, of the lived process, of the experience. The methodology consists of a theoretical production, characterized as a bibliographic and documentary study. The research points to the relevance of radical and inclusive pedagogy in the search for a more conscious state of being and depressing the human. Changes are proposed in the educational area and premises are sought for a collective construction, for an open society, with an impactful and innovative vision. The importance of the pedagogue and his role in the search to strengthen and expand bonds within the perspective of popular education, defending the freedom and autonomy brought by Freire and the mediator of Feuerstein as a key point for this process to occur. [resumo fornecido pelo autor]
A presente dissertação investiga de que maneira a mediação pedagógica na educação pré-natal pode contribuir a partir da perspectiva de uma educação popular. Pensar possibilidades de apoio e potencialização do objeto de estudo que investiga os princípios, as práticas de cuidado com os usuários frente aos programas de saúde pública. Analisa-se a mediação pedagógica enquanto potencial junto à educação pré natal; verifica-se a importância da mediação que se destaca enquanto horizonte para a educação pré-natal e para a educação popular, enquanto espaço pedagógico. Trago o seguinte problema de pesquisa: de que maneira a mediação pedagógica na educação pré-natal pode contribuir a partir da perspectiva de uma educação popular? Para o desenvolvimento, tem-se como objetivo geral analisar a mediação pedagógica enquanto potencial junto à educação pré-natal, pautada na perspectiva da educação popular. Para alcançar o objetivo geral, selecionaram-se os objetivos específicos: caracterizar a pedagogia radical enquanto possível horizonte para a educação pré natal; contextualizar a educação pré-natal enquanto experiência em saúde pública e a possível inserção do pedagogo fundamentado na concepção da educação e na educação pré-natal; verificar a importância da mediação da aprendizagem para os processos de educação pré-natal; destacar a mediação da aprendizagem enquanto horizonte para a educação pré-natal e a educação popular, no contexto de saúde enquanto espaço pedagógico. Como aporte teórico apresento os temas radicais defendidos pelo professor Dr. Agustín de la Herrán Gascón, que analisa dentro de um ponto de vista epistemológico e científico o desenvolvimento da educação pré-natal. Reuven Feuerstein, com suas produções e discussões sobre a mediação, além do processo enquanto capacidade de transformação de humano nos processos emocionais e cognitivos. Paulo Freire, no que concerne ao espaço de excelência à educação popular, oferecendo condições de reflexão frente a essa concepção, do processo vivido, da experiência. A metodologia consiste em uma produção de cunho teórico, caracterizando-se como estudo bibliográfico e documental. A pesquisa aponta como relevância a pedagogia radical e inclusiva na busca de um estado mais consciente ao ser e de desopressão do humano. Propõem-se mudanças na área educacional e buscam-se premissas para um construir coletivo, para uma sociedade aberta, com visão impactante e inovadora. A importância do pedagogo e sua atuação na busca por fortalecer e expandir vínculos dentro da perspectiva da educação popular, defendendo a liberdade e autonomia trazidas por Freire e o mediar de Feuerstein como ponto-chave para que esse processo possa ocorrer. [resumo fornecido pelo autor]
Keywords: Cuidado pré-natal - Educação; Educação popular; Educação inclusiva; Mediação; Pedagogos; Prenatal care - Education; Popular education; Inclusive education; Mediation; Pedagogues